Providing Help by the Means of Live Space Map in Intercultural Counselling - Słowik, Aneta (INSTED: Interdisciplinary Studies in Education & Society, 2012)
A modern human being is more and more often aware that they have to come to terms with the ambiguity and multidimensional character of ?events? in their own biography. However, a new ?organisation? of one?s life requires to undertake actions and educational efforts to ?tell? one?s own biography, which is accompanied by active formulation (but also solution) of problems. The counsellors who work with people coming from other cultural areas than they do, seek methods and tools which will be effective in the work with ?non-traditional? people who seek guidance. Such a possibility ?is provided? by the method of live space map, which may be treated not only as a method of work in the counselling field, but also as a way of acquiring biographic knowledge in the process of learning. The educational episodes which appear in life and problems connected thereto are treated as challenges and should be considered by individuals in the category of educational chances.